Implementasi Customer Relationship Menejemen Kepala Sekolah dalam Meningkatkan Jumlah Peserta Didik di SD Negeri 4 Mekarsari Cimerak - Kamaludin Kamaludin; Irpan Ilmi; Yayat Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study focuses on the implementation of Customer Relationship Management (CRM) by the Principal in an effort to increase the number of new students at SD Negeri 4 Mekarsari. SD Negeri 4 Mekarsari has experienced fluctuations in the number of participants in the last three years. Fluctuations in the number of participants are due to competition in each school competing for the attention and trust of parents to send their children to school. The research method used is a qualitative method with a descriptive approach. Data were collected through in-depth interviews with the Principal, teachers, school committees, and parents of students, as well as through observation and documentation. The analysis was carried out based on the policy implementation theory put forward by Jones and Charles O., which divides the implementation process into three stages: interpretation, organization, and application. And the CRM theory put forward by Gordon which includes Technology, People, Process, Knowledge. The results of the study indicate that the implementation of CRM at SD Negeri 4 Mekarsari includes a clear understanding at the interpretation stage, has succeeded in ensuring that all stakeholders understand the purpose and importance of CRM. At the organizational stage, the school has formed a structure that supports the implementation of CRM, including the formation of SOPs and resource allocation. However, at the application stage, it was found that despite the increase in the number of new students, CRM implementation still needs to be improved, especially in innovation and more optimal use of technology.